Estimación de parámetros reproductivos de la liebre europea (Lepus europaeus Pallas, 1778) en la provincia de Buenos Aires, Argentina - Martínez, H. S. (2003)
The reproduction of the European hare (Lepus europaeus) was studied in the Province of Buenos Aires, Argentina, over a complete annual cycle (1986 - 1987), for a total of 559 animals. The beginning of the breeding season at early winter period (May - June) could be determined, as well as the end of it at the beginning of the autumn (February - March), followed by a recess in the reproductive activity from March to May. Gonad weight and volume, as well as presence or absence of sperm and corpora lutea for males and females respectively, were taken into account as active reproduction indicators. Over a gestation period of 42 days, the pregnancy percentage was 54.9% for adult females in a seven-month reproductive period. The index of births was 2.75, with an average of 2.07 embryos per litter, and the final ratio of young per adult female was 5.7 a year. No statistically significant differences were found in the ratio of males to females in an annual cycle (1: 1.09). Eyes lens weight and ossification of the epiphyseal cartilage of the ulna and radius were used in order to determine the age.